On the Possible Astronomical Function of Portasar’s (Göbekli Tepe) Pillar 27 - Malkhasyan, H. A.
The examination of Portasar’s Pillar 27 in Enclosure C from an archaeoastronomical point of view reveals four distinct directions. Considering the directions obtained as observational shows that they could have served to observe the simultaneous culminations of Pleiades, α Persei, and 36 Draconis pointing towards the North Ecliptic Pole during the activity period of the September ε-Perseid meteor shower. On the same day (perhaps a few days apart) before sunrise, it was most likely possible to observe the star disappearance of the constellations Hercules and Centaurus at their culmination points. At the same time, the T-shaped structure of Pillar 27 could serve as a shadow meter (gnomon) to show the specified day of the mentioned observations. Additionally, 36 days after the summer solstice (Perseids activity period), the simultaneous appearance of the stars β Andromedae and γ Draconis at their culmination points was observable. On the other hand, there are principal parallels with the possible observations with the help of Portasar’s Pillar 27 and the function of Platform 3 (as well as some angular stones (No. 7, 12, 158, etc.)) of the Zorats Qarer megalithic monument, which refer to the same millennium (9000 BC). There are also commonalities with ancient calendar patterns that relate to ancient mythological concepts. Their detailed analysis is still in progress.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture